2022
DOI: 10.1177/03635465221110214
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Heavy Slow Resistance Training Combined With Corticosteroid Injections or Tendon Needling in Patients With Lateral Elbow Tendinopathy: A 3-Arm Randomized Double-Blinded Placebo-Controlled Study

Abstract: Background: Lateral elbow tendinopathy is a disabling tendon overuse injury. It remains unknown if a corticosteroid injection (CSI) or tendon needling (TN) combined with heavy slow resistance (HSR) training is superior to HSR alone in treating lateral elbow tendinopathy. Purpose/Hypothesis: The purpose was to investigate the effects of HSR combined with either (1) a CSI, (2) TN, or (3) placebo needling (PN) as treatment for lateral elbow tendinopathy. We hypothesized that 12 weeks of HSR in combination with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…Altas x et al 36 compared a home exercise program alone (26 patients) with an exercise program combined with either kinesiotaping (26 patients) or dry nee-dling (26 patients) and found that the exercise program plus dry needling group performed the best overall at 3 weeks and 6 months, with the exercise program plus kinesiotaping and dry needling groups both having significantly better outcomes than the home exercise program alone. Couppé et al 37 compared patients randomized to receive a corticosteroid injection (21 patients), tendon needling (17 patients), or placebo needling (20 patients), followed by a home exercise program, and did not find an additional benefit from either the corticosteroid or tendon needling through 12 months.…”
Section: Elbowmentioning
confidence: 99%
“…Altas x et al 36 compared a home exercise program alone (26 patients) with an exercise program combined with either kinesiotaping (26 patients) or dry nee-dling (26 patients) and found that the exercise program plus dry needling group performed the best overall at 3 weeks and 6 months, with the exercise program plus kinesiotaping and dry needling groups both having significantly better outcomes than the home exercise program alone. Couppé et al 37 compared patients randomized to receive a corticosteroid injection (21 patients), tendon needling (17 patients), or placebo needling (20 patients), followed by a home exercise program, and did not find an additional benefit from either the corticosteroid or tendon needling through 12 months.…”
Section: Elbowmentioning
confidence: 99%
“…Researchers from Copenhagen (Denmark) have performed and reported one of the best pieces of evidence surrounding treatment in this common, but often recalcitrant, condition. 2 Their three-arm, randomized, double-blinded, placebo-controlled trial was designed to study corticosteroid and TN in conjunction with HSR, as compared with placebo needling (PN) and HSR. They hypothesized that injection or needle therapy would be superior compared to placebo.…”
Section: Resistance Training Combined With Corticosteroid Injections ...mentioning
confidence: 99%